2022
DOI: 10.1002/cctc.202200595
|View full text |Cite
|
Sign up to set email alerts
|

An Environmentally Sustainable Synthesis of Enantioenriched CF3‐Chromanol, Indanol and Tetralol Derivatives by Rh‐Catalyzed Asymmetric Transfer Hydrogenation

Abstract: The Rh(III)-catalyzed asymmetric reduction of α-trifluoromethyl ketones through transfer hydrogenation was developed under mild conditions to access a series of enantioenriched cistrifluoromethyl alcohols via a dynamic kinetic resolution process. The reaction was efficiently performed in the green solvent 2-MeTHF with HCO 2 H/Et 3 N (1 : 1) as the hydrogen source. High yields, alongside excellent diastereo-and enantioselectivities were obtained for the synthesis of CF 3 -chromanol, CF 3 -indanol and CF 3 -tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Homochiral fluorinated alcohols, which are considered to be emerging structural motifs in medicinal chemistry (Cotman, 2021), can be obtained in high yields employing dynamic kinetic resolution (DKR) with Noyori-Ikariya asymmetric transfer hydrogenation (ATH) (Betancourt et al, 2021;Cotman et al 2022;Molina Betancourt et al, 2022). When Ru II -catalyzed DKR-ATH was applied to CF 3 CO-substituted benzofused cyclic ketones, it was observed that single or double reduction occurs, yielding either diastereo-and enantiopure monoalcohols or 1,3-diols (Cotman et al, 2016).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Homochiral fluorinated alcohols, which are considered to be emerging structural motifs in medicinal chemistry (Cotman, 2021), can be obtained in high yields employing dynamic kinetic resolution (DKR) with Noyori-Ikariya asymmetric transfer hydrogenation (ATH) (Betancourt et al, 2021;Cotman et al 2022;Molina Betancourt et al, 2022). When Ru II -catalyzed DKR-ATH was applied to CF 3 CO-substituted benzofused cyclic ketones, it was observed that single or double reduction occurs, yielding either diastereo-and enantiopure monoalcohols or 1,3-diols (Cotman et al, 2016).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…With the aim of continuing our investigations into the synthesis of fluorinated carbocycles and heterocycles [13][14][15][16][17], we envisaged to focus on a synthetic pathway for the fluorination of an isoxazole functionalized at C-5 by an acetal fragment, an area that has been relatively overlooked in the literature despite numerous molecules of interest featuring this motif (Figure 1) [18][19][20][21][22][23]. The synthesis of 4-fluorinated 3,5-disubstituted isoxazole was reported by either condensation of 2-fluoro-1,3-diketone [24,25] or gold-catalyzed cascade cyclization-fluorination of 2alkynone O-methyl oximes [26] but only one method for the direct fluorination in this position was reported relying on the use of Selectfluor as the fluorinating agent and delivering the desired products in moderate chemical yields ranging from 16% to 44% (Figure 2) [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…However, not only does this chemocatalytic protocol require the use of precious and difficult-to-remove metal components but also only one class of diastereoselectivity is usually inherently preferred, thus placing a formidable challenge for stereodivergent synthesis which is important for evaluating the structure–activity relationship to advance drug discovery and chemobiological studies . In addition, transition metal-catalyzed asymmetric hydrogenation often proceeds under forcing pressure or high temperature conditions, thus limiting the functional-group compatibility for certain substrates such as fluorine or fluoroalkyl-functionalized ones due to troublesome fluorine elimination . Notably, the incorporation of fluorine atoms into small molecules often imparts a profound impact on the physicochemical, pharmaceutical, and/or physiological properties of parent compounds in drugs and agrochemicals, thus stimulating interests for the synthesis of organofluorine substances .…”
Section: Introductionmentioning
confidence: 99%